(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
Responsible citizenship is vital for national development, social harmony, and global peace. In a rapidly evolving world where materialism and individualism often overshadow civic responsibility, there is an urgent need to reorient education systems to emphasize moral and ethical values. Valuesbased education (VbE) offers a holistic approach to developing individuals who are not only academically competent but also ethically sound and socially responsible. This article explored how VbE can be employed to cultivate responsible citizenship, examined its theoretical foundations, and provided practical strategies for implementation in educational institutions. The major challenges to its realization were cultural and contextual diversity, ambiguity in defining core values, teacher preparedness and competence, conflict with academic priorities, among others. However, the practical approaches to resolving these challenges include teacher training, policy support, community involvement, and the strategic use of media and digital tools and as well as school administrators’ involvement through continuous monitoring and evaluation system to assess effectiveness of valuebased education and the use of feedback mechanisms from students, staff, parents and other stakeholders to strengthen value-related programs.